The Effect Of Moral Obligation, Tax Sanctions, And Service Digitalization On Motor Vehicle Taxpayer Compliance In Bogor City - Laxsmi, Amelia; Pamungkas, Bambang; Asfiya, Nurul (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Motor vehicle tax is a tax imposed on the ownership and/or possession of motor vehicles. This tax is one of the provincial local taxes. Tax compliance refers to the extent to which taxpayers comply with applicable tax regulations. Taxpayer compliance is influenced by various factors. This study aims to investigate the influence of moral obligation, tax sanctions, and service digitization on the compliance of motor vehicle taxpayers in the city of Bogor. This research adopts a quantitative approach with the population being all motor vehicle taxpayers in the city of Bogor, and the sample consisting of 100 respondents obtained using the Solvin formula. Data collection is done through questionnaires and analyzed using multiple linear regression tests. Data processing utilizes the Statistical Package for the Social Sciences (SPSS) version 26. The results of this study indicate that, partially, moral obligation, tax sanctions, and service digitization have an impact on the compliance of motor vehicle taxpayers. Simultaneously, moral obligation, tax sanctions, and service digitization collectively influence the compliance of motor vehicle taxpayers.